2020
DOI: 10.1002/htj.21681
|View full text |Cite
|
Sign up to set email alerts
|

Constructal design of longitudinally finned tubes cooled by forced convection

Abstract: The constructal design method is used in the present study to find the configuration of longitudinally finned tubes cooled by forced convection. The finned tubes are arranged in parallel inside a fixed two-dimensional domain. Two degrees of freedom inside the domain are considered for the design. The first degree of freedom is the tube-to-tube spacing, and the second is the length of the longitudinal fin.For both these degrees of freedom, a three-fin position inside the domain is considered. The fin is placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The finite volume method with SIMPLE algorithm is used to solve the three-dimensional governing Equations ( 7)- (11). These equations are firstly transformed from the physical domain of coordinates (X, Y, Z) to the computational domain of body-fitted coordinates (ζ, η, Z).…”
Section: Numerical Procedure Grid Test and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The finite volume method with SIMPLE algorithm is used to solve the three-dimensional governing Equations ( 7)- (11). These equations are firstly transformed from the physical domain of coordinates (X, Y, Z) to the computational domain of body-fitted coordinates (ζ, η, Z).…”
Section: Numerical Procedure Grid Test and Validationmentioning
confidence: 99%
“…Other constructal designs for single and multiscale tubes and fins are found in Mustafa and colleagues. [7][8][9][10][11][12][13] On the other side, there were many numerical and experimental studies of heat exchangers with circular fins. Mon and Gross 14 investigated numerically the forced convection from a four-row heat exchanger with circular fins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the optimal fins number occurred at ( N = 6) with angle between the fins (10°). Constructal design from single‐scale tubes with different shapes in forced and natural convections can be found in Mustafa and colleagues 10–14 . Constructal design of cavities can be seen in Lorenzini and colleagues 15,16 …”
Section: Introductionmentioning
confidence: 99%
“…Constructal design from singlescale tubes with different shapes in forced and natural convections can be found in Mustafa and colleagues. [10][11][12][13][14] Constructal design of cavities can be seen in Lorenzini and colleagues. 15,16 Several multiscale constructal designs for fins are exist in the literature.…”
Section: Introductionmentioning
confidence: 99%